IMPLEMENTATION OF SISTER CITY COOPERATION IN BANDUNG CITY AND BRAUNSCHWEIG CITY IN 2019-2021 - Kusumaningjati, Wisnu Teja (Prodi Ilmu Hubungan Internasional, Universitas Fajar, 2024)
Bandung collaborates with the city of Braunschweig in Germany in the form of sister city cooperation. The background to the sister city cooperation carried out by the two cities is the similarity in administrative systems, culture and education centers. Sister city cooperation is a manifestation of paradiplomacy. In the implementation process, this sister city cooperation program experienced developments in many fields. Therefore, researchers want to see how paradiplomacy is implemented in the sister city cooperative relationship carried out by the City of Bandung and the City of Braunschweig. The author uses analysis of paradiplomacy theory and international cooperation. The research method used in this research is a qualitative research method with primary data sources originating from related websites and also secondary data sources from news and previous research. The research technique used is literature review. From the results of the research that has been carried out, it can be seen that the implementation of paradiplomacy in sister city cooperation between the City of Bandung and the City of Braunschweig can be said to be successful and has had a positive impact on each city. Keywords: City of Bandung, City of Braunschweig, International Cooperation, Paradiplomacy, Sister City